Estimation of optimal nasotracheal tube depth in adult patients - Ji, Sung-Mi (J Dent Anesth Pain Med, 2017)
BACKGROUND: The aim of this study was to estimate the optimal depth of nasotracheal tube placement. METHODS: We enrolled 110 patients scheduled to undergo oral and maxillofacial surgery, requiring nasotracheal intubation. After intubation, the depth of tube insertion was measured. The neck circumference and distances from nares to tragus, tragus to angle of the mandible, and angle of the mandible to sternal notch were measured. To estimate optimal tube depth, correlation and regression analyses were performed using clinical and anthropometric parameters. RESULTS: The mean tube depth was 28.9 ± 1.3 cm in men (n = 62), and 26.6 ± 1.5 cm in women (n = 48). Tube depth significantly correlated with height (r = 0.735, P < 0.001). Distances from nares to tragus, tragus to angle of the mandible, and angle of the mandible to sternal notch correlated with depth of the endotracheal tube (r = 0.363, r = 0.362, and r = 0.546, P < 0.05). The tube depth also correlated with the sum of these distances (r = 0.646, P < 0.001). We devised the following formula for estimating tube depth: 19.856 + 0.267 × sum of the three distances (R(2) = 0.432, P < 0.001). CONCLUSION: The optimal tube depth for nasotracheally intubated adult patients correlated with height and sum of the distances from nares to tragus, tragus to angle of the mandible, and angle of the mandible to sternal notch. The proposed equation would be a useful guide to determine optimal nasotracheal tube placement.